Co-Expression of VAL- and TMT-Opsins Uncovers Ancient Photosensory Interneurons and Motorneurons in the Vertebrate Brain - Fischer, Ruth M.; Fontinha, Bruno M.; Kirchmaier, Stephan; Steger, Julia; Bloch, Susanne; Inoue, Daigo; Panda, Satchidananda; Rumpel, Simon; Tessmar-Raible, Kristin (PLOS Biology, 2013)
Evolutionarily conserved, nonvisual opsins appear to endow specific interneurons and motorneurons of the vertebrate brain with light sensitivity, suggesting that environmental light may be able to modulate information processing.